Analisis Keputusan Investasi Saham Syariah Periode 2020-2024 dengan Pendekatan Sharia Compliant Asset Pricing Model (SCAPM) - Amalia, Firdha; Khatimah, Husnul; Hardiansyah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Potential investors are required to be able to process information and be able to see investment opportunities that can produce optimal levels of return with minimal levels of risk so that they can provide large profits in the future. Rate of return (return) and risk (risk) are two fundamental things in investing. The samples chosen in this research were fourteen stock companies that were consistently listed on the Jakarta Islamic Index (JII) in the 2020-2024 period. The criteria for determining investment decisions in this research is selecting efficient stocks that have individual returns that are higher than the expected return [(Ri) > E(Ri)]. The results of calculations using the Sharia Compliant Asset Pricing Model (SCAPM) method show that five companies are included in the efficient stock group category, including ADRO, INCO, PGAS, PTBA and UNTR. Of the five company shares, ADRO shares have a greater individual share rate of return than the other four efficient shares. So the investment decision that investors must take is to buy ADRO shares